2007
DOI: 10.1200/jco.2007.10.8126
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection After Rescue Cetuximab Treatment for Colorectal Liver Metastases Previously Refractory to Conventional Systemic Therapy

Abstract: For CLM refractory to conventional chemotherapy, combination therapy with cetuximab increases resectability rates without increasing operative mortality or liver injury. The median OS and PFS of 20 and 13 months, respectively, suggest that this novel oncosurgical strategy benefits patients with previously refractory disease who respond subsequently to cetuximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(99 citation statements)
references
References 23 publications
4
88
0
7
Order By: Relevance
“…In fact, recently, the introduction of cetu and beva to the standard chemotherapy has further improved survival. The safety of major hepatic resection in the setting of neo-adjuvant chemotherapy is crucial and still unknown when considering the use of these new "targeted molecules" (12)(13)(14)(15)(16). This case-control study did not show any deleterious consequences on outcomes after hepatic resection when cetu or beva were added to the standard chemotherapy regimen.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In fact, recently, the introduction of cetu and beva to the standard chemotherapy has further improved survival. The safety of major hepatic resection in the setting of neo-adjuvant chemotherapy is crucial and still unknown when considering the use of these new "targeted molecules" (12)(13)(14)(15)(16). This case-control study did not show any deleterious consequences on outcomes after hepatic resection when cetu or beva were added to the standard chemotherapy regimen.…”
mentioning
confidence: 71%
“…Oxaliplatin-based regimens have been associated with an increased risk of vascular lesions (sinusoidal obstruction syndrome (SOS)) (6-9) and irinotecan-containing regimens have been also associated with increased risks of steatosis and steatohepatitis (Chemotherapyassociated steato-hepatitis (CASH)) (8)(9). Preliminary results demonstrated that the addition bevacizumab or cetuximab to conventional chemotherapy may further increase the response rates (10)(11)(12). Few studies reported the outcome of liver resection after use of bevacizumab in combination with chemotherapy (13,14) and only two studies (15,16) reported the effect of bevacizumab on the non-tumorous liver.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…It is concluded that cetuximab when combined with firstline chemotherapy increases the possibility of resection for patients with initially unresectable liver without increasing surgical mortality or liver injury [15].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-operative irinotecan was associated with steatohepatitis and patients with this liver injury had higher 90-day mortality (Vauthey et al, 2006). Neoadjuvant cetuximab was not found to be associated with specific pathological liver damage yet (Adam et al, 2007). These studies highlighted the importance of chemotherapy-induced damage on the non-tumour bearing liver -a complication that needs to be carefully assessed in future studies.…”
Section: What Are the Current Controversies With Resection Of Colorecmentioning
confidence: 93%
“…Although bevacizumab did not significantly improve ORR when added to oxaliplatin/fluoropyrimidine com-pared with oxaliplatin/fluoropyrimidine alone in the NO16966 study, there was a numerical increase in the curative surgery rate in the bevacizumab-containing arm (19.2 vs 12.9%), although this was a post hoc analysis. Even in patients resistant to initial chemotherapy, one study showed that subsequent addition of cetuximab to chemotherapy induced a response and allowed 12% of patients to proceed to surgery with a median OS of 20 months (Adam et al, 2007) and no increase in peri-operative mortality. Currently there is no universally agreed optimal conversion chemotherapy before resection of liver metastasis.…”
Section: What Are the Current Controversies With Resection Of Colorecmentioning
confidence: 99%